Dose estimation for bivalirudin during pediatric cardiopulmonary bypass. Issue 6 (4th February 2021) - Wolstencroft, Philip; Arnold, Philip; Anderson, Brian J.
Abstract: Aim: A typical adult‐based bivalirudin regimen during cardiopulmonary bypass uses a loading dose of 1 mg kg −1 and a circuit prime (volume L × 13 mg) with a subsequent intravenous infusion 2.5 mg h −1  kg −1 . Dose in children remains unknown. We wished to determine a practical bivalirudin dosing schedule for children undergoing surgery with cardiopulmonary bypass. Methods: Published pharmacokinetic parameters in children who were anticoagulated for cardiac catheterization using bivalirudin were compared to adult by scaling for size using allometry. An infusion regimen suitable for children was determined using a bivalirudin target concentration (13 mg L −1 ) common in adults for effect during cardiopulmonary bypass. Predicted bivalirudin infusion rates in children were compared to regimens published as case reports. Results: Current pediatric bivalirudin infusion rates are based on those used in adults with titration during cardiopulmonary bypass to achieve activated clotting times longer than 400 s. Bivalirudin clearance (mL min −1  kg −1 ) can be estimated in children by scaling adult parameters using allometry. Clearance decreases through childhood and higher infusion rates in children would achieve target concentration rapidly without the need to titrate initial infusion rate. An infusion rate of 4.5 mg h −1  kg −1 in a 10 kg infant, 4 mg h −1  kg −1 in a 20 kg child and 3.5 mg h −1  kg −1 in a child 30–40 kg will target an activated clotting time slower than 400 s. Adult regimens could be used in those children heavier than 50 kg. Conclusion: Bivalirudin infusion in children should be started after loading dose at rates greater than those used in adults. Dose in neonates remains uncertain because neither pharmacokinetics nor coagulation pharmacodynamics have been adequately characterized.